Arterial Anastomosis Using Microsurgical Techniques in Adult Live Donor Liver Transplant: A Focus on Technique and Outcomes at a Single Institution - Huang, Samantha; Fahradyan, Artur; Ahearn, Aaron; Kaur, Navpreet; Sher, Linda; Genyk, Yuri; Emamaullee, Juliet; Patel, Ketan; Carey, Joseph N. (Journal of Reconstructive Microsurgery, 2022)
Background Microvascular hepatic artery reconstruction (MHAR) is associated with decreased rates of hepatic artery thrombosis (HAT) in living donor liver transplantation (LDLT). There is a paucity of literature describing the learning points and initiation of this technique at the institutional level. The objective of this study is to report our institutional experience using MHAR in adult LDLT with a focus on technique and outcomes.Methods A retrospective review of adult patients who underwent LDLT from January 2012 to December 2020 was conducted. Patients were divided into two groups, those who underwent LDLT without MHAR and with MHAR. We analyzed cases for technical data including donor and recipient artery characteristics, anastomotic techniques, intraop events, and postop complications. A Mann–Whitney test was performed to compare outcomes between non-MHAR and MHAR patients.Results Fifty non-MHAR and 50 MHAR patients met inclusion criteria. Median age at transplantation was 58 (interquartile range [IQR] 11.8) and 57.5 years (IQR 14.5), respectively. Median follow-up for MHAR patients was 12.8 months (IQR 11.6). The most common recipient arteries were the right hepatic artery (HA) (58%) and left HA (20%). Median size of recipient and donor arteries were 3.3 mm (IQR 0.7) and 3.1 mm (IQR 0.7), resulting in a median mismatch size of 0.3 mm (IQR 0.4). Median microanastomosis time was 44 minutes (IQR 0). HAT, graft failure, and mortality rates were higher in the non-MHAR cohort (6% vs. 0%, 8% vs. 0%, and 16% vs. 6%, respectively); however, these did not reach statistical significance.Conclusion This study found lower rates of HAT and graft failure after implementing MHAR, though statistical significance was not achieved. Larger cohort studies are needed to further assess the potential benefit of MHAR in adult LDLT. From our experience, MHAR requires cooperation between the transplant and microsurgical teams, with technical challenges overcome with appropriate instrumentation and planning.
Keywords: microsurgery; surgery; liver; transplant; live donor liver transplant